Bifidobacterium bifidum as an example of a specialized human gut commensal - Turroni, Francesca; Duranti, Sabrina; Bottacini, Francesca; Guglielmetti, Simone; Van Sinderen, Douwe; Ventura, Marco (Frontiers in Microbiology, 2014)
Bifidobacteria are considered dominant and for this reason key members of the human gut microbiota, particularly during the first one to two years following birth. A substantial proportion of the bifidobacterial population in the intestine of infants belong to the Bifidobacterium bifidum taxon, whose members have been shown to display remarkable physiological and genetic features involving adhesion to epithelia, as well as utilization of host-derived glycans. Here, we reviewed the current knowledge on the genetic features and associated adaptations of B. bifidum to the human gut.